55.8k views
2 votes
How would you solve this question?

How would you solve this question?-example-1
User Latrisha
by
5.2k points

1 Answer

3 votes

Answer:

The value of a is and b is e.

The steps are :

First, you have to integrate the expression shown in the first picture.

Next, you have to solve it as simultaneous equation shown in the second picture.

You have to apply :


ln(b) - ln(a) = ln( (b)/(a) )


ln(y) = x \: ⇒ \: {e}^(x) = y

How would you solve this question?-example-1
How would you solve this question?-example-2
User WelcomeTo
by
5.1k points